OVERALL RESOURCE EFFECTIVENESS (ORE) INDICES FOR TOTAL RESOURCE MANAGEMENT AND CASE STUDIES - Chien, Chen-Fu; Chu, Pei-Chun; Zhao, Lizhong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
High-tech industries are capital-intensive, in which capital effectiveness and productivity are critical for maintaining competitive advantages. Most of the existing studies focused on demand forecast, capacity planning, order allocation, and capacity management to enhance capital effectiveness. Few approaches are developed to address productivity and resource management, while one of critical roles for industry engineers is to enhance productivity and resource utilization effectiveness in practice. This study aims to propose a set of novel indices for Overall Resource Effectiveness (ORE) and drive various improvement directions for total resource management. A number of case studies are reviewed for illustration, while the proposed methodology is extended for medical instrument for cross validation. The results have shown practical viability of the proposed ORE to drive collaborative efforts to enhance total productivity and overall resource effectiveness. This paper concludes with discussions on value propositions of proposed ORE indices and future research directions.